Supramolecular Approaches for Taming the Chemo- and Regiochemistry of C60 Addition Reactions - Beil, Sebastian B.; von Delius, Max (Organic Materials, 2021)
The chemo- and regioselective functionalization of fullerenes is a long-standing problem of organic synthesis. Over the past five years, this fundamental challenge has gained technological relevance, because studies on single bis-adduct isomers in new-generation solar cells have demonstrated that the widespread use of isomer mixtures leads to suboptimal power conversion efficiencies. Herein, we review recent work on supramolecular approaches for achieving chemo- and regioselective syntheses of multiply functionalized derivatives of C60.
Keywords: fullerenes; template effect; supramolecular chemistry; regioselectivity; organic photovoltaics; host–guest chemistry